Temporal pattern of production subcontracting in Nigeria (2002)
This paper examines the temporal trend, that is, the growth in production subcontracting over the years in Nigeria. The relevant concepts are production subcontracting and diffusion of innovation. Data were collected from the sixty-eight contracting firms among 15 industrial estate/areas in the Lagos region. This paper shows that the growth in the number of contractors/subcontractors, which was gradual at the initial stage, became more rapid thereafter. The results of the regression/correlation analyses carried out, using the year as the dependent variable and the number of contractors/subcontractors as the independent variable are significant at 0.0001 per cent level at both the aggregate level and the level of the Lagos region. The study shows that if encouraged, production subcontracting could be used to enhance the industrial development of Nigeria.